Zadovoljstvo pacientov z informacijskim sistemom eZdravje v splošni bolnišnici - Kodermac, Nena (Obzornik zdravstvene nege, 2024)
Introduction: The introduction of digitalisation in health care has transformed the system of healthcare appointment scheduling. The aim of this study was to describe the level of patient satisfaction with the eHealth information system in a selected healthcare institution, and to identify potential shortcomings of this system.Methods: The study included 319 randomly selected patients awaiting medical treatment at "Dr Franc Derganc" General Hospital in Nova Gorica during a one-month period in 2023. A 15-item questionnaire was administered to respondents and a high reliability coefficient was calculated (Cronbach's alpha = 0.894). Basic descriptive statistics and Pearson's correlation analysis were used for the statistical analysis.Results: Our respondents were generally satisfied with the eHealth services ( = 4.18, s = 0.69); however, their satisfaction was observed to decrease with age (r = –0.166, p = 0.00). They showed a high degree of autonomy in relation to eAppointment scheduling (82.8%, n = 264). Among the different services offered by the system, respondents were most satisfied with information about medical treatment ( = 4.45, s = 0.57), and least satisfied with information about the use of eHealth provided in their primary care physician's office.Discussion and conclusion: The results indicate that the majority of respondents have already used eHealth, but many still schedule their healthcare appointments by telephone. This emphasises the need to raise public awareness of the diverse options and methods of scheduling healthcare appointments.
Keywords: e-services; informatika; kakovost; nursing; quality; zdravstvena nega